"Ghost patrol" - Newfield, Sam, 1899-1964; Gittens, Wyndham; McCoy, Tim; Excelsior Pictures Corp.; Cinetel Films ([Los Angeles, CA] : Excelsior Pictures Corp., 1936)
A professor invents a radium tube that makes planes internal combustion engines stop running. He and his invention are captured by a gang of robbers. A federal agent is sent to rescue him. --
Originally released as a motion picture in 1936.
Tim McCoy, Claudia Dell, Walter Miller, Wheeler Oakman, Jimmy Burtis, Lloyd Ingraham, Dick Curtis.
Cinematographer, Jack Greenhalgh; editor, Jack English.
In English.
Online resource; title from opening/closing credits (Digitalia Film Library, viewed December 4, 2015).
Keywords: Thieves -- Drama; Science fiction films; Western films; Feature films; Internet videos; Streaming video